Documentación para el periodismo especializado. - Chacón Gutiérrez, Inmaculada (Revista General de Información y Documentación, 2001)
The information needs of specialised journalism are analysed and sorne of the sources which journalists can use in different information areas are given, thereby offering a general review of the documentary elemenís in this context. The aim is to give the reader a guide, not only to where the documentation of specialised information is lo be found but also to the information sources to be used, not forgetting the new information products and services on the Internet. Also presented is a series of web sites for each of the different kinds of journa lism described.
Keywords: Documentation; Journalistic Documentation; Specialised Journalism; Informative Documenration